VALIDATION OF QUALITY CONTROL METHODS OF INJECTION SOLUTION "DALEN" (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In recent years, the demand for hemostatic medicinal products has increased significantly. This trend is associated with a number of medical and social factors. Bleeding conditions are frequently encountered in surgical practice, traumatology, obstetrics and gynecology, as well as in diseases accompanied by disorders of the blood coagulation system. Therefore, the need for effective and safe hemostatic agents remains high.
Keywords: oncological diseases, cardiovascular disorders, and pathologies